Identification of Wnt-5a Receptors Important in Diabetic and Non-Diabetic Corneal Epithelial Wound Healing - Ruchi Shah; Cynthia Amador; Adam J. Poe; Tanya M. Spektor; Priyanka Bhandary; Yizhou Wang; Zhiping Paul Wang; Daniel J. Weisenberger; Vanessa Borges; Onkar B. Sawant; Ezra Maguen; Pedram Hamrah; et al. (2025)
Purpose: Persistent epithelial alterations such as delayed wound healing are a key feature of diabetic corneal disease. Previously, we reported that epigenetic changes in the diabetic cornea led to the suppression of Wnt-5a, and that addition of Wnt-5a accelerated wound healing. In this study, we set to determine which Wnt receptor(s) mediated Wnt-5a induced stimulation of diabetic corneal epithelial wound healing. Methods: Human limbal epithelial cells (LECs) were isolated from postmortem diabetic and non-diabetic donor eyes for single-cell RNA sequencing (scRNA-seq) and DNA methylation analysis. These analyses were validated by qRT-PCR, western blot, or immunostaining of corneal tissue sections. Cultured primary LECs were transfected with small interfering RNA (siRNA) to specific Wnt receptors to evaluate their role in scratch wound healing in the presence or absence of 200 ng/mL Wnt-5a. Results: Single-cell RNA sequencing analysis revealed differential gene expression of Wnt receptors, ROR2, MCAM, FZD5, FZD6, and FZD7. DNA methylation arrays showed hypomethylation of ROR2 gene promoter in diabetic versus non-diabetic LECs by 41.3% (**P < 0.01) resulting in increased ROR2 protein expression. Non-diabetic cells transfected with siRNA to knockdown ROR2 but not FZD5, FZD6, FZD7, MCAM, and RYK showed significantly decreased wound healing by approximately 50% (*P < 0.05) versus control siRNA. In diabetic LECs, knockdown of ROR2 significantly inhibited wound healing by 40% (*P < 0.05) and of FZD5 partially blocked wound healing that could not be restored by the addition of Wnt-5a. Conclusions: Wnt-5a seems to mediate wound healing in diabetic LECs mainly through receptor tyrosine kinase like orphan receptor 2 with Frizzled-5 serving as a possible co-receptor with a smaller effect.